Expanding the Classroom: Local Government Practitioners' Use of Academic Resources - Jacobson, Willow S.; Lambright, Kristina T. (Journal of public affairs education : J-PAE., 2017)
Drawing on E. L. Boyer's Scholarship Reconsidered (1990), we propose that public affairs education could be conceptualized to include the education of not just current students but also practitioners throughout their careers. To explore knowledge diffusion from academics to such practitioners, we conducted 40 phone interviews with county human resources (HR) directors in New York and North Carolina and examined the extent to which this population directly used academic resources. There was moderate use of academic resources from higher-education institutions across the sample; many North Carolina HR directors consulted publications and personnel from one university that offers tailored services for local government officials in that state. Several HR directors who do not use academic resources indicated that they would be willing to do so. At the same time, many respondents were unsure what academic resources were available or when they would be helpful.